Вплив Європейського Зеленого курсу на сільськогосподарське виробництво - Каминіна, Олександра Костянтинівна (My University, 2024)
The European Green Deal (EGD) significantly impacts EU agri-food production. This thesis analyzes policy frameworks promoting sustainable practices and resource efficiency. Agri-food producers face both challenges and opportunities: stricter regulations require adjustments, but offer potential for increased efficiency, higher product value, and certifications. Innovation and knowledge transfer are crucial. New technologies like precision agriculture are key to achieving EGD’s environmental and resource efficiency goals. A Plzeňský Prazdroj case study showcases successful EGD implementation through renewable energy, sustainable packaging, and ambitious emissions reduction targets. Collaboration, political support, and a holistic approach are needed to achieve the EGD’s goals. The EGD’s focus on sustainability presents a path for a long-term, resilient EU agri-food sector.
Effects of the European Green Deal on agricultural production
Keywords: Зелений курс; агропродовольча сфера; сталість; політика; інновація; технологія; ЄС; Zelená dohoda; agropotravinárstvo; udržateľnosť; politika; inovácie; technológie; EÚ; Green Deal; agri-food; sustainability; policy; innovation; technology; EU